Chloroplast genome of Thesium chinense: The insight into phylogeny of Santalaceae - Zhenyu Zhao; Hongxiu Li; Meilan Chen; Meng Cheng; Cadiz Quispe Gustavo Pedro; Xiuteng Zhou; Luqi Huang (KeAi Communications Co., Ltd., 2023)
Thesium chinense is an important and commonly used traditional Chinese medicine. The aim of this study is to obtain more bioinformatics from Thesium chinense and to conduct a more comprehensive and in-depth analysis of Santalaceae's phylogeny. This study sequenced the chloroplast genome of Thesium chinense and performed bioinformatics analysis on its key genes to reconstruct the Santalaceae phylogenetic tree. The genes of traditional Chinese medicine often affect the generation and accumulation of metabolic products. The different genes in the chloroplast genome of Thesium chinense have different biological characteristics. The phylogenetic system of Santalaceae and its related families differs significantly from classical classification. This study has laid a solid foundation for the better application and identification of Thesium chinense.